Congenital Deformities of the Upper Limbs. Part III: Overgrowth; Undergrowth; Streeter and Others() - Bisneto, Edgard Novaes França (Rev Bras Ortop, 2013)
This article, presented in three sections, review the most commons upper limb malformations and theirs treatments. In this section three there's a discussion about overgrowth; undergrowth; Streeter Syndrome and other malformations. The bibliography is continuous since section one.